2023
DOI: 10.1007/s00234-023-03139-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between computed tomography perfusion and the effect of intravenous alteplase prior to endovascular treatment in acute ischemic stroke

Abstract: Purpose Intravenous alteplase (IVT) prior to endovascular treatment (EVT) is neither superior nor noninferior to EVT alone in acute ischemic stroke patients. We aim to assess whether the effect of IVT prior to EVT differs according to CT perfusion (CTP)–based imaging parameters. Methods In this retrospective post hoc analysis, we included patients from the MR CLEAN-NO IV with available CTP data. CTP data were processed using syngo.via (version VB40). We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…These results were confirmed by Porto and colleagues in a study from the Stroke Thrombectomy and Aneurysm Registry (STAR) database [146] . The equivalence between NCCT ASPECTS and CTP criteria for patient’s selection was also confirmed in the early time window [147] , [148] , [149] . Next, Bouslama and colleagues demonstrated that ischemic core volume automatically calculated with Brainomix software and CTP DEFUSE 3 target mismatch measured with RAPID were equivalent in predicting final infarct volume [150] .…”
Section: Imaging Modalities For the Selecion: Conventional Versus Adv...mentioning
confidence: 64%
“…These results were confirmed by Porto and colleagues in a study from the Stroke Thrombectomy and Aneurysm Registry (STAR) database [146] . The equivalence between NCCT ASPECTS and CTP criteria for patient’s selection was also confirmed in the early time window [147] , [148] , [149] . Next, Bouslama and colleagues demonstrated that ischemic core volume automatically calculated with Brainomix software and CTP DEFUSE 3 target mismatch measured with RAPID were equivalent in predicting final infarct volume [150] .…”
Section: Imaging Modalities For the Selecion: Conventional Versus Adv...mentioning
confidence: 64%